IMPROVING STUDENTSâ SPEAKING SKILL BY USING ROLE â PLAY METHOD AT CLASS X SENIOR HIGH SCHOOL 9 MERANGIN - Yulianti, Emi (Reflective, 2012)
This research is based on the problem found at class X Senior High School 9 Merangin. From the result of first observation was found that studentsâ speaking skill in class X program have obstructions. One of those is less self skill from them to be active in English speaking class. The purpose of this research is improving studentsâ speaking skill by using role play method. The Classroom Action Research was done and the researcher did the teaching with the help of English teacher as the collaborator. The finishing indicated that the givin role play to the students role play method has a positive result to their speaking skill. It can be seen from the test result at the last meeting of cycle 2 showed that more than 70% students class X has fulfilled the indicator score of success. It can be concluded that by giving role play method can improve studentsâ speaking skill at class X Senior High School 9 Merangin.